Critical Success Factors For Hybrid Cloud Data Integration: A Case Study In The Cement Industry - Agil Angga Saputra; Achmad Nizar Hidayanto; Rani Fersari Damanik; Nurul Nadiyatun Sholihah; Dandi Taufiqurrohman (UNIVERSITAS PAKUAN, 2026)
Data integration in hybrid cloud environments is a major challenge in the era of digital transformation due to the need to manage data efficiently across both public and private cloud environments. This study aims to identify and rank the Critical Success Factors (CSFs) for data integration in hybrid cloud environments, using a case study of PT XYZ, which is currently undergoing a cloud migration process. The study integrates three frameworks: TOE (Technology–Organization–Environment), HOT-fit (Human–Organization–Technology), and the IS Triangle, to form a holistic evaluation model with five dimensions. Twenty CSF factors were identified through a literature review and validated through interviews with five experts. Subsequently, the Analytical Hierarchy Process (AHP) method was applied to a questionnaire distributed to ten expert respondents to rank these factors. Of the five dimensions, the Business dimension was found to be the most important (weight 0.33), followed by Environment (0.18), Organization (0.17), Technology (0.17), and Human (0.15). These findings provide practical guidance for organizations implementing hybrid cloud data integration, particularly within the context of Indonesian regulations.